Associations Between Data Driven Dietary Patterns at Age 71 and the Prevalence of Sarcopenia 16 Years Later: A Cohort Study. (7th June 2021) - Karlsson, Mikael; Becker, Wulf; Cederholm, Tommy; Byberg, Liisa
Abstract: Objectives: Unlike physical activity, the role of diet in sarcopenia is unclear, and studies have predominantly focused on effects of single nutrients. Therefore, we assessed the associations between adherences to data driven dietary patterns (DPs), and the prevalence of sarcopenia (and its constituents) 16 years later. Methods: Four DPs were defined using principal component analysis based on information from a 7-day food record retrieved from 1133 men (average age 71 years) in the Uppsala Longitudinal Study of Adult Men. Associations of each DP with sarcopenia 16 years later (defined according to the European Working Group on Sarcopenia in Older People; EWGSOP2) were analyzed using multivariable logistic regression ( n  = 257). Associations of each DP with muscle strength, muscle mass and physical performance 16 years later were analyzed using multivariable linear regression. We applied two models when adjusting for potential confounders: one unadjusted for potential confounders and one adjusted for age at baseline, follow-up period, reported energy intake at baseline, education, physical activity level at baseline, smoking, morbidity at baseline and BMI at baseline. Results: The prevalence of sarcopenia at follow-up was 19% (50/257). Associations were largely non-linear and DPs were categorized into low, medium and high adherence. Compared to low adherence, medium and high adherence to DP2 (i.e., vegetables, green salad, fruit, poultry, rice and pasta) was associated with lower odds ratio (OR) of sarcopenia; adjusted ORs: 0.41 (95% confidence interval [CI]: 0.17–0.98) and 0.40 (95% CI: 0.17–0.94), respectively. There was a tendency that a higher adherence to a DP mainly characterized by a consumption of potato, meat and egg, and low consumption of fermented milk (DP4) was associated with higher prevalence of sarcopenia (low vs high adherences; adjusted OR: 1.61, 95% CI: 0.67 - 3.87). The other DPs displayed no clear associations. The analyses of DPs in relation to the individual sarcopenia constituents indicated no clear associations. Conclusions: Dietary patterns may be a contributing modifiable cause of sarcopenia. Funding Sources: The Uppsala Geriatric Foundation and the Region Örebro County supported this work.